Partial discharge evaluation of a high voltage transformer - Kyere, Isaac Kwabena (My University, 2015)
This dissertation is devoted to the study of partial discharge evaluation of a high voltage transformer. The 400 V/300 000 V (300 kV) high voltage transformer in the high voltage laboratory was manufactured in 1967. Given the old age of the transformer and the crucial importance of insulation systems, it is vital to assess the condition of its insulation to ensure the effectiveness and the reliability of the transformer as well as the safety of the personnel using it. In order to achieve that, it is important to evaluate the partial discharge in the insulation system as this is the main cause of destruction of insulation. The phase-resolved partial discharge method was the main method used to perform the partial discharge measurements in this research. Partial discharge measurements were performed on a faulty 11 kV voltage transformer. Defects were also created in samples of solid insulation at predetermined locations with different shapes and sizes. The measurements taken on the 11 kV voltage transformer and samples of solid insulation formed a basis to prove the validity of the assessment methods on the 300 kV transformer. Using the method mentioned above, partial discharges were recorded with respect to the phase of the applied voltage with the aid of a commercial instrument which complies with IEC 60270, (ICM monitor - partial discharge detector from Power Diagnostix Systems GmbH). The observations from this study have furthered the understanding of partial discharge processes. The patterns recorded were analysed in order to conclude about the condition of the transformer. From the partial discharge pattern, the type and location of partial discharges were concluded. The patterns obtained from the transformer reveal that the device is healthy and can be operated up to 200 kV.
M. Tech. (Power Engineering Department, Faculty of Engineering and Technology) -- Vaal University of Technology
Keywords: High voltage transformer; Partial discharge; Insulation; 621.314; Transformers, Electric.; High voltages.